Ultra-processed foods consumption is associated with multiple sclerosis severity - Guglielmetti, Monica; Grosso, Giuseppe; Ferraris, Cinzia; Bergamaschi, Roberto; Tavazzi, Eleonora; La Malfa, Alessandro; Wahidah, H. Al-Qahtani; Tagliabue, Anna (Frontiers in Neurology, 2023)
Background MS is a chronic inflammatory neurological and immune-mediated disease of multifactorial etiology. Ultra-processed foods (UPFs) have been generally considered unhealthy due to their poor nutritional value. Emerging evidence suggests that factors other than their nutritional content may play an additional role toward chronic inflammation. Aim To investigate the potential association of UPF consumption and MS severity in a group of MS Italian consecutive patients. Methods Demographic (age, sex, marital status, educational level), neurological (EDSS, MSSS), and nutritional (anthropometric measures, dietary habits) information were collected. Physical activity and smoking habits were also investigated. Food items were grouped according to the NOVA classification. Patients were classified in two groups based on MS severity (“mild” and “moderate to high”). Results Higher UPF consumption was associated with moderate-to-high MS severity compared to lower consumption in both the unadjusted model (OR = 2.28, 95% CI: 1.04–5.01) and after adjustment for potential background (OR = 2.46, 95% CI: 1.04–5.83) and clinical confounding factors (OR = 2.97, 95% CI: 1.13–7.77). Conclusions Although these results are only preliminary and hypothesis generating, it is important to explore how various aspects of the diet may relate to MS severity in order to identify the best strategy to support MS patients over the disease course.